Efek Simvastatin terhadap Urin dan Jaringan Buli-Buli pada Tikus Model Sistitis Interstisial Akut yang Diinduksi Protamin Sulfat - Hasanuddin, Abdi Dzul Ikram; Minhajat, Rahmawati; Muis, Mirna (Alami Journal (Alauddin Islamic Medical) Journal, 2023)
The pathophysiology of interstitial cystitis (IC) is complicated and related to statin drug use without any established underlying mechanisms. This study used a rat model of acute IC caused by protamine sulfate to examine the effects of simvastatin on bladder and urine macro-tissue after simvastatin treatment. There were 12 adult female Wistar rats. Simvastatin 10 mg/kgBB + protamine sulfate group (S10P), Simvastatin 50 mg/kgBB + protamine sulfate group (S50P), and Placebo + Protamin Sulfate group (KP) were the three groups (each n=4) into which the subjects were grouped. Simvastatin or placebo CMC 0,5% was administered orally to all animals for 30 days, followed by an intravesical protamine sulfate (10 mg/ml) instillation procedure. All animals were gathered three days after intravesical therapy to collect urine samples and bladder tissue. Simvastatin group participants' levels of hematuria were significantly higher than those of the control group (p = 0.03). Only relative bladder weight was substantially higher in the S50P group than in the control group (p=0.032). Simvastatin group members did not substantially vary from the control group regarding bladder macroscopic oedema and haemorrhage. To conclude, simvastatin may influence the condition of tissue hypervascularization and hypertrophy, contributing to the chronicity of acute interstitial cystitis.